The Continued Promise and Many Disappointments of Oncolytic Virotherapy in Gastrointestinal Malignancies - Daniel H. Ahn; Tanios Bekaii-Saab (Biomedicines, 2017)
Oncolytic virotherapy represents a novel therapeutic strategy in the treatment of gastrointestinal malignancies. Oncolytic viruses, including genetically engineered and naturally occurring viruses, can selectively replicate in and induce tumor cell apoptosis without harming normal tissues, thus offering a promising tool in the armamentarium for cancer therapy. While this approach has garnered much interest over the past several decades, there has not been significant headway across various tumor types. The recent approval of talimogene laherparepvec, a second-generation oncolytic herpes simplex virus type-1, for the treatment of metastatic melanoma, confirms the therapeutic potential of oncolytic viral therapy. Herein, we will highlight and review the role of oncolytic viral therapy in gastrointestinal malignancies while discussing its limitations and potential alternative mechanisms to improve its treatment efficacy.